INFORMATION Equivalence of stochastic processes - A. V. Ausiannikau (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The necessary theoretical knowledge to obtain and analyze the information function of the stochastic process is shown. The concept of information equivalence of stochastic processes on the individual parameters of these processes is introduced. The definition of information equivalence of stochastic processes is given. The method of information equivalent formation to stochastic processes is considered. The examples of calculation and analysis of information functions of stationary and non-stationary processes are submitted.